Ascariasis in a 75-year-old man with small bowel volvulus: a case report - Romano, Giovanni (2021)
Background: Ascaris lumbricoides and Ascaris suum are the most common soil-transmitted helminths of humans and pigs, respectively. The zoonotic potential of A. suum has been a matter of debate for decades. This study was aimed to present a case of human ascariasis caused by A. suum in southern Italy. Case presentation: A 75-year-old man presented to the department of surgery in Avellino (southern Italy) complaining of abdominal pain and vomiting. Physical examination revealed bloating and abdominal tenderness. A computed tomography scan showed air-fluid levels and small bowel distension. During exploratory laparotomy a small bowel volvulus with mesenteritis was evident and surprisingly an intraluminal worm was detected. The worm was removed with a small enterotomy and identified as an adult female of A. suum based on morphological and molecular analysis. Faecal examination revealed the presence of unfertilized Ascaris eggs with an intensity of 16 eggs per gram (EPG) of faeces. The patient was treated with mebendanzole 100 mg twice a day for 3 days. The post-operative course was regular with re-alimentation after 3 days and discharge after 12 days. Conclusions: This report shows as A. suum can function as a relevant agent of human zoonosis. Therefore, in patients with bowel obstruction with no evident aetiology a helminthic infestation should be considered for an accurate diagnosis, especially in patients living in rural areas.